2008
DOI: 10.1074/jbc.m705822200
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene E4 Activates Peroxisome Proliferator-activated Receptor γ and Induces Prostaglandin D2 Generation by Human Mast Cells

Abstract: sensitive to interference by the PPAR␥ antagonist GW9662 and to targeted knockdown of PPAR␥. Although LTE 4 -mediated PGD 2 production was also sensitive to MK571, an antagonist for the type 1 receptor for cys-LTs (CysLT 1 R), it was resistant to knockdown of this receptor. This LTE 4 -selective receptor-mediated pathway may explain the unique physiologic responses of human airways to LTE 4 in vivo.Cysteinyl leukotrienes (cys-LTs) 2 (LTC 4 , LTD 4 , LTE 4 ) are potent inflammatory mediators derived from arachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
116
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(121 citation statements)
references
References 61 publications
5
116
0
Order By: Relevance
“…In contrast, LTE 4 failed to activate a CysLTR in human pulmonary vessels (Walch et al, 2002). In 2008, the first report that LTE 4 mediated prostaglandin D 2 production, which was sensitive to the CysLT 1 R antagonist MK-571 but resistant to knock down of this receptor, was published (Paruchuri et al, 2008). Furthermore, this effect, induced through COX-2 induction and ERK, p90RSK, and cAMP-regulated-binding protein phosphorylation, was not mediated by LTD 4 but was sensitive to PPAR-␥ knockdown, suggesting the 568 presence of a LTE 4 -selective receptor in human MCs (Paruchuri et al, 2008).…”
Section: Leukotriene E 4 Receptor(s)mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, LTE 4 failed to activate a CysLTR in human pulmonary vessels (Walch et al, 2002). In 2008, the first report that LTE 4 mediated prostaglandin D 2 production, which was sensitive to the CysLT 1 R antagonist MK-571 but resistant to knock down of this receptor, was published (Paruchuri et al, 2008). Furthermore, this effect, induced through COX-2 induction and ERK, p90RSK, and cAMP-regulated-binding protein phosphorylation, was not mediated by LTD 4 but was sensitive to PPAR-␥ knockdown, suggesting the 568 presence of a LTE 4 -selective receptor in human MCs (Paruchuri et al, 2008).…”
Section: Leukotriene E 4 Receptor(s)mentioning
confidence: 99%
“…In 2008, the first report that LTE 4 mediated prostaglandin D 2 production, which was sensitive to the CysLT 1 R antagonist MK-571 but resistant to knock down of this receptor, was published (Paruchuri et al, 2008). Furthermore, this effect, induced through COX-2 induction and ERK, p90RSK, and cAMP-regulated-binding protein phosphorylation, was not mediated by LTD 4 but was sensitive to PPAR-␥ knockdown, suggesting the 568 presence of a LTE 4 -selective receptor in human MCs (Paruchuri et al, 2008). Almost simultaneously it was demonstrated that intradermal injection of LTE 4 into the ear of mice deficient in both CysLT 1 R/CysLT 2 R elicited a vascular leak that exceeded the response to intradermal injection of LTC 4 or LTD 4 and that this response was inhibited by pretreatment of the mice with PTX or a Rho kinase inhibitor (Maekawa et al, 2008).…”
Section: Leukotriene E 4 Receptor(s)mentioning
confidence: 99%
“…The biased nature of agonist signaling through one receptor (Violin and Lefkowitz, 2007) is not without precedence; the -opioid receptor (Keith et al, 1996) is one well characterized example. These results with LTE 4 are significant given the recent de- termination of a (putative) LTE 4 -selective receptor (CysLT E ) and that LTE 4 can apparently act via non-GPCR pathways (e.g., peroxisome proliferator-activated receptor-␥) (Paruchuri et al, 2008). LTE 4 signaling via the hCysLT 2 receptor apparently displays preference toward trimeric G-protein signaling rather than via ␤-arrestin 2 pathways, as evidenced by the calcium activity but lack of ␤-arrestin 2 association.…”
Section: Discussionmentioning
confidence: 88%
“…The cysteinyl LT binds to the cysteinyl LT receptors 1, 2, and 3 or the cysteinyl LT receptor E4. [35][36][37] Cysteinyl LTs evoke contradictory effects on vascular tone, depending on the species and the experimental preparations, 38) via both endothelium-and smooth muscle-dependent actions. The functional roles of these cysteinyl LT receptors in regulation of pulmonary vessels still remain unknown.…”
Section: Discussionmentioning
confidence: 99%